Lead Time From First Suspicion Of Malignant Melanoma In Primary Care To Diagnostic Excision: A Cohort Study Comparing Teledermatoscopy And Traditional Referral To A Dermatology Clinic At A Tertiary Hospital - Karina Schultz; Lina U Ivert; Jan Lapins; Karin Sartorius; Emma K Johansson (Dermatology Practical & Conceptual, 2023)
Introduction The increasing use of teledermatoscopy in clinical practice has led to demands to evaluate the effects of this new technology on traditional healthcare systems.